CHARACTERIZATIONS FOR SEVERAL CLASSES OF ALTERNATIVE CODES - Ngo, Hien Thi (Journal of Computer Science and Cybernetics, 2017)
Alternative codes, an extension of the notion of ordinary codes, have been first introduced and considered by P. T. Huy et al. in 2004. In this paper, we consider some new subclasses of alternative codes. In particular, characteristic properties and a hierarchy of such codes are established. Also, algorithms to test for these classes of codes are proposed.